Obesity and Right Ventricular Structure and Function: The MESA-Right Ventricle Study - Chahal, Harjit (American College of Chest Physicians, 2012)
BACKGROUND: The relationship between obesity and right ventricular (RV) morphology is not well studied. We aimed to determine the association between obesity and RV structure and function in a large multiethnic population-based cohort. METHODS: The MESA-Right Ventricle Study measured RV mass and volumes by cardiac MRI in participants aged 45 to 84 years without clinical cardiovascular disease in the Multi-Ethnic Study of Atherosclerosis (MESA). Participants were divided into three categories based on BMI: lean ( ≤ 24.9 kg/m(2)), overweight (25-29.9 kg/m(2)), and obese ( ≥ 30 kg/m(2)). RESULTS: The study sample included 4,127 participants. After adjustment for demographics, height, education, and cardiovascular risk factors, overweight and obese participants had greater RV mass (6% and 9% greater, respectively), larger RV end-diastolic volume (8% and 18% greater, respectively), larger RV stroke volume (7% and 16% greater, respectively), and lower RV ejection fraction ( ≥ 1% lower) than lean participants (all P < .001). These findings persisted after adjusting for the respective left ventricular (LV) parameters. CONCLUSIONS: Overweight and obesity were independently associated with differences in RV morphology even after adjustment for the respective LV measure. This association could be explained by increased RV afterload, increased blood volume, hormonal effects, or direct obesity-related myocardial effects.